Nitrogen uptake rates and phytoplankton composition across contrasting North Atlantic Ocean coastal regimes north and south of Cape Hatteras - Zhu, Yifan; Mulholland, Margaret R.; Bernhardt, Peter W.; Neeley, Aimee Renee; Widner, Brittany; Tapia, Alfonso Macías; Echevarria, Michael A. (Frontiers in Microbiology, 2024)
Understanding nitrogen (N) uptake rates respect to nutrient availability and the biogeography of phytoplankton communities is crucial for untangling the complexities of marine ecosystems and the physical, biological, and chemical forces shaping them. In the summer of 2016, we conducted measurements of bulk microbial uptake rates for six 15N-labeled substrates: nitrate, nitrite, ammonium, urea, cyanate, and dissolve free amino acids across distinct marine provinces, including the continental shelf of the Mid-and South Atlantic Bights (MAB and SAB), the Slope Sea, and the Gulf Stream, marking the first instance of simultaneously measuring six different N uptake rates in this dynamic region. Total measured N uptake rates were lowest in the Gulf Stream followed by the SAB. Notably, the MAB exhibited significantly higher N uptake rates compared to the SAB, likely due to the excess levels of pre-existing phosphorus present in the MAB. Together, urea and nitrate uptake contributed approximately 50% of the total N uptake across the study region. Although cyanate uptake rates were consistently low, they accounted for up to 11% of the total measured N uptake at some Gulf Stream stations. Phytoplankton groups were identified based on specific pigment markers, revealing a dominance of diatoms in the shelf community, while Synechococcus, Prochlorococcus, and pico-eukaryotes dominated in oligotrophic Gulf Stream waters. The reported uptake rates in this study were mostly in agreement with previous studies conducted in coastal waters of the North Atlantic Ocean. This study suggests there are distinct regional patterns of N uptake in this physically dynamic region, correlating with nutrient availability and phytoplankton community composition. These findings contribute valuable insights into the intricate interplay of biological and chemical factors shaping N dynamics in disparate marine ecosystems.